2012
DOI: 10.1117/1.jbo.17.12.128003
|View full text |Cite
|
Sign up to set email alerts
|

Real-time phase-contrast imaging of photothermal treatment of head and neck squamous cell carcinoma: anin vitrostudy of macrophages as a vector for the delivery of gold nanoshells

Abstract: Photothermal treatment (PTT) using nanoparticles has gained attention as a promising alternative therapy for malignant tumors. One strategy for increasing the selectivity of PTT is the use of macrophages as a cellular vector for delivering nanoparticles. The aim of the present study is to examine the use of macrophages as a cellular vector for efficient PTT and determine the appropriate irradiation power and time of a near-infrared (NIR) laser using real-time phase-contrast imaging. Thermally induced injury an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
3
24
1
Order By: Relevance
“…Most previous studies were confined to in vitro studies [16]. In our last study, we confirmed the possibility of using macrophages as live vectors for the delivery of nanoparticles and identified the optimal conditions for PTT to selectively kill cancer cells around nanoshell (NS)-loaded macrophages in an in vitro model [17]. It is only recently that the feasibility of the in vivo treatments has been investigated.…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…Most previous studies were confined to in vitro studies [16]. In our last study, we confirmed the possibility of using macrophages as live vectors for the delivery of nanoparticles and identified the optimal conditions for PTT to selectively kill cancer cells around nanoshell (NS)-loaded macrophages in an in vitro model [17]. It is only recently that the feasibility of the in vivo treatments has been investigated.…”
Section: Introductionsupporting
confidence: 50%
“…In the previous in vitro study [17], we found that for optimal PTT performance the concentration of NSs should be around 27.5 pM and the number of macrophage cells should be 2 × 10 4 cells. The NS suspension was co-incubated with peritoneal macrophages with gentle shaking in a 15-mL tube for 1 hour.…”
Section: Uptake Of Nss By the Peritoneal Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to achieve desired effects, different groups have reported either use of prolonged exposure time with laser, extreme high laser power, or an excessive amount of nanoparticles, making it a challenge for use in vivo and/or clinics. 18,19,[35][36][37] We have comparatively summarized the use of a number of different nanoparticles in targeted and untargeted in vitro experiments in Supplemental Data S3. To approach these difficulties, we have developed a targeted nanoparticle approach of using a tumor-specific targeting moiety conjugated to PEG-functionalized MWCNTs.…”
Section: Discussionmentioning
confidence: 99%
“…42 In the case of nanoshells, it is possible to modulate the relative contribution of the absorption or scattering of the particle by manipulating only the core/shell ratio and keeping the particle size unchanged. 43,44 Nanoshells, as nanoscale heat sources, are currently being exploited in photothermal cell death and tumor destruction in vitro, [45][46][47] with some other minor potential applications such as exogenous absorbers for tissue welding. 48,49 In addition to being used as heating sources, these particles are either exploited as contrast agents, optically adjusted across a broad range of wavelengths in comparison with conventional molecular contrast agents.…”
Section: Introductionmentioning
confidence: 99%